Anisotropic scattering in radio-echo sounding: insights from northeast Greenland - T. A. Gerber; T. A. Gerber; D. A. Lilien; D. A. Lilien; N. F. Nymand; D. Steinhage; O. Eisen; O. Eisen; D. Dahl-Jensen; D. Dahl-Jensen (The Cryosphere)
Anisotropic scattering and birefringence-induced power extinction are two distinct mechanisms affecting the azimuthal power response in radio-echo sounding (RES) of ice sheets. While birefringence is directly related to the crystal orientation fabric (COF), anisotropic scattering can, in principle, have various origins. We use curve-fitting techniques to evaluate the relative contributions of anisotropic scattering and birefringence in quad-polarized ground-based RES measurements from the Northeast Greenland Ice Stream (NEGIS), identifying their dominance and orientation across depths of 630–2500 m. We find that anisotropic scattering clearly dominates the radar signal in most depths larger than 1200 m, while birefringence effects are most important in shallower depths and particularly in the vicinity of the ice-stream shear margins. We further find that the co-polarized power difference follows the ice-sheet stratigraphy with a notable transition in strength and/or direction at the Wisconsin–Holocene transition and in folded ice outside the ice stream, possibly indicating disrupted stratigraphy in these folded units. We conclude that small-scale fluctuations in the horizontal COF eigenvalues are the most likely mechanism responsible for the anisotropic scattering observed in our survey area. Mapping the strength and orientation of scattering in quad-polarized measurements thus has the potential to provide independent estimates of the COF orientation and distinguish ice units with different scattering properties, e.g. from different climatic periods.